Primary School Students' Knowledge About Menarche and Their Readiness: A Comparative Study - Kusuma Wijaya Ridi Putra; Fakhrun Nisa’ Fiddaroini; Vendi Eko Kurniawan (Public Health of Indonesia)
Background: Menarche represents a critical developmental milestone in the lives of young girls, often accompanied by a range of emotional responses influenced by the level of knowledge and preparedness. Inadequate preparation and prevalent misconceptions may contribute to heightened anxiety and suboptimal menstrual hygiene practices, particularly in low- and middle-income settings.